Cuando se abran las puertas de una gran casa: el hospital de Braga (siglos XVII-XVIII) - Araújo, Maria Marta Lobo de (2019)
This paper seeks to analyse the inside of the São Marcos hospital during the Modern Age and to introduce not only its different spaces but also all the objects used on a daily basis. So, we shall analyse the infirmaries particularly the furniture, clothes, beds, as well as the pilgrims quarters, the kitchen, the pharmacy, the cloister, and both the chaplain and the provider’s ‘houses’. We shall try to share a thought on the distribution of these spaces by analysing simultaneously the renovation programs they have been submitted to throughout the past two centuries. We shall also pay attention to their different functionalities, more precisely as regards the residents and the travellers. We shall also have the chance to connect the degree of sociability between hospital users. Finally, we shall stress the hospital’s other function: the salvation of the soul.